Fire performance in buildings : academic insights and perspective analysis - Oliveira, Rejane Martins Viegas de (2022)
Accelerated growth of urbanization and the consequent rise in the number of buildings results on an increase in rapid constructions without minimum criteria that enable the safe building performance and how it behaves during episodes of fire. In this scenario, this paper aims to analyze research trends and the status quo of building fire performance in the last five years, evaluating perspectives for research, and proposals for future directions through a Systematic Literature Review (SLR) approach associated with bibliometric analysis. The analysis was carried out based on the Web of Science database under parameters such as authors, countries and regions, journals, research areas, and keywords. For each rule, among all the results retrieved, those that stood out the most in the stipulated period were evaluated. It was found that research on fire performance in projects is increasing, with a total of 402 published works. In the analysis by Systematic Literature Review, there was a trend of research concerning materials and structural systems, evaluating the performance, behavior, resistance, and safety of buildings under fire conditions. Ultimately, the results pointed out a possible evolution of the trend in research on methodologies and intelligent control systems applied to the management of fire emergencies.